ChemInform Abstract: Aromatics to Bis‐triquinane: A Tandem Oxidative Dearomatization of Bis‐Phenol, Cycloaddition, Photorearrangement and a Rapid Entry into Carbocyclic Framework of Xeromphalinone E. Issue 48 (2nd December 2014) - Singh, Deepak; Chaudhari, Umesh V.; Deota, Pradeep T.
Abstract This describes attempts to synthesize compound (I), which is structurally related to Xeromphalinone E.